Application of mNGS in the Etiological Diagnosis of Thoracic and Abdominal Infection in Patients With End-Stage Liver Disease - Chen, Hongmei; Zhang, Ye; Zheng, Jie; Shi, Lei; He, Yingli; Niu, Yinghua; Lei, Jine; Zhao, Yingren; Xia, Han; Chen, Tianyan (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Despite the obvious advantages of metagenomic next-generation sequencing (mNGS) in etiological diagnosis of various infectious diseases, there are few reports on etiological diagnosis of suspected thoracic and abdominal infections in patients with end-stage liver disease (ESLD). Methods: 73 ESLD patients were enrolled from January 2019 to May 2021 due to suspected complicated thoracic and abdominal infections with poor response to empirical anti-infective treatment. Pleural effusion and ascites samples of these patients were collected for mNGS detection and conventional pathogens culture. The application value of mNGS in etiological diagnosis of thoracic and abdominal infections in ESLD patients was finally evaluated. Results: A total of 96 pathogens were detected using mNGS method, including 47 bacteria, 32 viruses, 14 fungi, 2 M. tuberculosis, and 1 parasite. The positive rate of mNGS reached 42.5%, which was significantly higher than that of conventional culture method (21.9%) (p=0.008). Considering neutrophil counts, the overall positive rate of bacteria detection of both methods in PMN≥250/mm3 group was 64.3%, and in PMN<250/mm3 group was 23.7%. Compared with the final clinical diagnosis, the agreement rate of mNGS in patients with positive bacteria detection and with suspected positive bacteria detection was 78.6% (11/14) and 44.4% (8/18), respectively. In addition, the agreement rate of mNGS was 66.7% (4/6, respectively) in patients with positive and suspected fungal detection. Interestingly, of the 11 patients with fungal detection, 5 had alcoholic liver disease, accounting for 45.5% of all patients with alcoholic liver disease. We also detected 32 strains of viruses using mNGS, mainly cytomegalovirus (62.5%). Conclusions: mNGS method is a useful supplement to conventional culture methods, which performs a higher positive rate, higher sensitivity, and broader pathogen spectrum, especially for rare pathogens and those difficult to culture. For ESLD patients, mNGS has great prospects in early etiological diagnosis of thoracic and abdominal infections. In addition, the cutoff values for the diagnosis of bacterial infection (PMN≥250/mm3) in the thoracic and abdominal cavities may need to be redefined.